Mutational analysis of Tyr-318 within the non-nucleoside reverse transcriptase inhibitor binding pocket of human immunodeficiency virus type I reverse transcriptase. - Pelemans, H; Esnouf, R; Jonckheere, H; De Clercq, E; Balzarini, J (1998)
The highly conserved Tyr-318 is part of the non-nucleoside reverse transcriptase inhibitor (NNRTI)-specific lipophilic pocket of human immunodeficiency virus type I reverse transcriptase (RT) and makes contact within 4 A with the NNRTIs in all reported RT/NNRTI complexes. Using site-directed mutagenesis, six mutant RTs were constructed bearing the mutations Y318H, Y318K, Y318L, Y318C, Y318W, and Y318F. We found that only the Y318W and Y318F mutant RTs retained substantial RT activity, whereas the catalytic activities of the Y318K, Y318C, Y318H, and Y318L RT mutants were less than 5% of the wild-type activity. The Y318F mutant RT retained substantial sensitivity to the majority of NNRTIs tested, whereas the Y318W mutant RT showed varying degrees of resistance to NNRTIs. Subunit-specific site-directed mutagenesis revealed that there was no difference in the catalytic activity or resistance/sensitivity spectrum toward NNRTIs regardless of whether the Tyr-318 mutation was introduced in both subunits or only in the p66 subunit of RT. Recombinant viruses harboring the Y318F or Y318W mutation in the RT showed a similar resistance/sensitivity pattern to NNRTIs as their corresponding 318 mutant recombinant RTs. Our findings stress a functional or structural role for Tyr-318 in wild-type RT and argue for the design of novel NNRTIs that interact more closely with this amino acid in the NNRTI-specific pocket of human immunodeficiency virus type I RT.